Virtual Learning Apps: Best Instructional Leadership Practices in the Digital Age Efforts to Improve Student Learning Outcomes - Irma Rachmawati Maruf; Budi Sulistiyo Nugroho; Andri Kurniawan; Zayid Musiafa; Erwinsyah Satria (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The Paper aimed to understand virtual learning applications, the best education practices in the all-digital era. The author believes that one element that leads to successful learning in the digital era is using some virtual learning applications. The researchers have explored many scientific publications looking for evidence of recent studies on how to benefit virtual learning from national and international publication literature databases. So that we can use the data to answer the problem of this study, first we try to explore the data by examining it to get an in-depth understanding of the clock such as data evaluation, data coding, in-depth interpretation, and good abstraction in answering the core problems of the study. After in-depth study and discussion, the data show that we are finally convinced that several applications that excel in virtual learning have been recommended by several education and technology experts due to their effectiveness and innovative power to provide best practices to improve student learning or learning outcomes. They added that typical learning in the digital era is the ability to choose and use several digital applications that have advantages in transforming learning in the 21st-century era. We are sure that the result and new evidence of this project would be used as input to develop similar studies in the future.